2021
DOI: 10.1111/obr.13160
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of school‐based interventions targeting physical activity, physical fitness or sedentary behaviour on obesity prevention in 6‐ to 12‐year‐old children: A systematic review and meta‐analysis

Abstract: A systematic search of the literature was performed to compare the effects of interventions that targeted sedentary behaviours or physical activity (PA) or physical fitness on primary prevention of obesity in 6-to 12-year-old children. The search identified 146 reports that provided relevant data for meta-analysis. Point estimates in % body fat were higher for fitness interventions compared with PA interventions (standardized mean difference = −0.11%; 95% CI = −0.26 to 0.04, and −0.04%; 95% CI = −0.15 to 0.06,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
1
26
1
1
Order By: Relevance
“…By sex, more females than expected in both groups decreased a body fat category, whereas males did not. This is consistent with Podnar and colleagues [42] systematic review that showed many school-based programs demonstrate a strong intervention effect in females and only borderline effects in males. This is interesting as females are commonly shown to engage in less MVPA than males throughout the day [28,43].…”
Section: Discussionsupporting
confidence: 92%
“…By sex, more females than expected in both groups decreased a body fat category, whereas males did not. This is consistent with Podnar and colleagues [42] systematic review that showed many school-based programs demonstrate a strong intervention effect in females and only borderline effects in males. This is interesting as females are commonly shown to engage in less MVPA than males throughout the day [28,43].…”
Section: Discussionsupporting
confidence: 92%
“…Interventions should include all stakeholders who engage with this serious health concern, including parents and educators. 10 , 14 …”
Section: Screen Time and The Physical Health Of Childrenmentioning
confidence: 99%
“…For instance, these reviews have only examined experimental study designs. Some reviews examined any school-related intervention [ 19 , 23 ], while the others were specific to recess [ 25 ], classrooms [ 22 , 26 ], or standing desks in particular [ 20 , 21 , 24 ]. The two reviews that examined any school-related interventions were specific to adiposity indicators in primary school-aged children [ 23 ], and physical activity in older adolescents [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews examined any school-related intervention [ 19 , 23 ], while the others were specific to recess [ 25 ], classrooms [ 22 , 26 ], or standing desks in particular [ 20 , 21 , 24 ]. The two reviews that examined any school-related interventions were specific to adiposity indicators in primary school-aged children [ 23 ], and physical activity in older adolescents [ 19 ]. Further, of the reviews examining a broad spectrum of health and well-being indicators, two were specific to standing desk interventions [ 20 , 24 ] and the other was specific to recess [ 25 ].…”
Section: Introductionmentioning
confidence: 99%